Comparison of golimumab 100-mg monotherapy to golimumab 50 mg plus methotrexate in patients with rheumatoid arthritis: Results from a multicenter, cohort study. Issue 1 (2nd January 2016) - Yonemoto, Yukio; Okamura, Koichi; Takeuchi, Kimihiko; Ayabe, Keio; Kaneko, Tetsuya; Matsushita, Masatoshi; Tamura, Yasuyuki; Iso, Takenobu; Okura, Chisa; Otsuka, Keiko; Inoue, Hiroshi; Takagishi, Kenji
Abstract : Objective. The aim of this study was to compare the efficacy and safety of golimumab (GLM) 50 mg + methotrexate (MTX) combination therapy and GLM 100 mg monotherapy in patients with rheumatoid arthritis (RA). Methods. The subjects were 115 RA patients (92 females and 23 males; median (range) age, 64 (17–87) years; median (range) disease duration, 8 (0.6–48) years) started on GLM. Eighty-three patients received GLM 50 mg/4 weeks + MTX (C group; median (range) MTX dosage 8 (2–16) mg/week), and 32 patients received GLM 100 mg/4 weeks (M group). Serum C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), matrix metalloproteinase-3, disease activity score (DAS) 28-ESR, DAS28-CRP, simplified disease activity index, and clinical disease activity index were evaluated 4, 12, and 24 weeks after starting GLM. Results. There were no significant differences in disease activity, adverse events, and drug continuation rates at 24 weeks between the groups. The DAS28-ESR remission rate was 34% in the C group and 26% in the M group. Conclusions. GLM 100 mg monotherapy improved disease activity as well as GLM 50 mg + MTX combination therapy. GLM 100 mg monotherapy appears to have a sufficient therapeutic effect in RA patients who cannot take MTX.